Inhibitory effect of ucha‐shinki‐hwan on cold‐mediated response in human dermal microvascular endothelial cells. Issue 2 (8th August 2017) - Lee, Kangwook; Cho, Sung‐Gook; Lee, Gyu Ri; Choi, Yu‐Jeong; Go, Ho Yeon; Sun, Seung‐Ho; Kim, Tae‐Hun; Park, Jong‐Hyeong; Choi, You‐Kyung; Lee, Hesol; Jung, Ki‐Yong; Song, Yun‐Kyung; et al.
ABSTRACT: Aim: Raynaud's phenomenon is characterized by prolonged vasoconstriction in cutaneous capillaries on cold stress. RhoA activity would be a therapeutic target for treating Raynaud's phenomenon. A traditional herbal medicine, ucha‐shinki‐hwan, has been used to promote vasodilation, but the biological mechanism of ucha‐shinki‐hwan is still unclear. Thus, we hypothesized that ucha‐shinki‐hwan is able to be used for treatment of Raynaud's phenomenon and that ucha‐shinki‐hwan inhibits cold‐induced vasoconstriction by targeting RhoA GTPase. Methods: Human dermal microvascular endothelial cells were pretreated with ucha‐shinki‐hwan for 30 min, followed by incubation in room temperature (37 ± 2°C) or a lower temperature (25 ± 2°C) for 30 min. Expression of active RhoA was measured on western blot. Endothelin‐1 and nitric oxide production were examined on enzyme‐linked immunosorbent assay. The formation of stress fiber and focal adhesion complex was analyzed using immunocytochemistry. Results: Cold exposure activated RhoA GTPase whereas ucha‐shinki‐hwan treatment suppressed its activation in human dermal microvascular endothelial cells. Moreover, ucha‐shinki‐hwan decreased cold‐induced endothelin‐1 and nitric oxide production. In addition, ucha‐shinki‐hwan treatment inhibited the formation of stress fiber and focal adhesion complex with downregulation of focal adhesion kinase (FAK), SRC kinase and extracellular regulated kinases (ERK) phosphorylation. Conclusion: Ucha‐shinki‐hwan inhibits contraction of cold‐exposed human dermal microvascular endothelial cells by targeting RhoA activation. This in vitro study is therefore the first to suggest that ucha‐shinki‐hwan is likely to be effective for inhibiting cold‐induced response in vascular endothelial cells.